2011
DOI: 10.1097/aln.0b013e318201f571
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic Epidural Anesthesia Improves Early Outcomes in Patients Undergoing Off-pump Coronary Artery Bypass Surgery

Abstract: Background:The aim of this two-center, open, randomized, controlled trial was to evaluate the impact of thoracic epidural anesthesia on early clinical outcomes in patients undergoing off-pump coronary artery bypass surgery. Methods: Two hundred and twenty-six patients were randomized to either general anesthesia plus epidural (GAE) (n ϭ 109) or general anesthesia only (GA) (n ϭ 117). The primary outcome was length of postoperative hospital stay. Secondary outcomes were: arrhythmia, inotropic support, intubatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
37
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 22 publications
5
37
1
2
Order By: Relevance
“…Recently, a prospective, randomized, controlled trial [26] has shown that the addition of TEA to conventional GA accounts for a significant reduction in the incidence of postoperative arrhythmias, and an improvement in the overall quality of recovery, allowing earlier tracheal extubation and earlier hospital discharge. In our study, GA plus TEA had no impact on the outcomes of OPCABs, while it lead to a higher requirement for vasoactive drug use.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a prospective, randomized, controlled trial [26] has shown that the addition of TEA to conventional GA accounts for a significant reduction in the incidence of postoperative arrhythmias, and an improvement in the overall quality of recovery, allowing earlier tracheal extubation and earlier hospital discharge. In our study, GA plus TEA had no impact on the outcomes of OPCABs, while it lead to a higher requirement for vasoactive drug use.…”
Section: Discussionmentioning
confidence: 99%
“…Analgesia with spinal opioids showed no effect on mortality, incidence of myocardial infarction, arrhythmias, mortality and duration of intubation when compared with general anesthesia (47). In patients undergoing off-pump coronary artery bypass surgery, the addition of thoracic epidural to general anesthesia can reduce the incidence of postoperative arrhythmias and improves pain control and overall quality of recovery, allowing earlier extubation and hospital discharge (48).…”
Section: Myocardial Protectionmentioning
confidence: 99%
“…Equal success has been achieved using both thoracic epidural anesthesia and general anesthesia techniques for OPCAB surgery (40,(47)(48)(49). OP-CAB with thoracic epidural anesthesia allows efficient cerebral blood flow management, reduces the rate of postoperative arrhythmias, and improves pain control with overall satisfactory recovery (45).…”
Section: Anesthetic Technique and Perioperative Challenges Of Opcabmentioning
confidence: 99%